HUBUNGAN EFIKASI DIRI DAN KUALITAS HIDUP LANSIA DENGAN HIPERTENSI DI PUSKESMAS CAKUNG, JAKARTA TIMUR - Bintang, Muhammad; Lestari, Puspita Hanggit; Maryam, Raden Siti; Badriah, Siti; Ekasari, Mia Fatma (Prodi Keperawatan Tegal Program Diploma III Poltekkes Kemenkes Semarang, 2025)
The quality of life related to health can be affected by disease conditions, one of which is hypertension. Hypertension can reduce the quality of life due to the impact of the disease itself as well as the consequences of the treatment carried out. Elderly people who have a poor quality of life can have a negative impact on their physical and mental health. The quality of life of the elderly with hypertension is influenced by various factors, one of which is self-efficacy. Self-efficacy makes an important contribution to understanding the process of behavior change, where high self-efficacy makes individuals feel capable of taking the necessary actions. The study was conducted to determine the relationship between self-efficacy and quality of life in the elderly with hypertension and the characteristics of the elderly, namely age, gender, and family caring for the elderly. This study is an observational analytical study with a bivariate Chi Square test. The sample in this study amounted to 106 elderly people who were selected using the Purposive Sampling method. Data was collected using questionnaires with instruments. Of the 106 elderly respondents in the Cakung Health Center area who became respondents, the results of the elderly who had high self-efficacy with the results of 65 (61.3%) were elderly, while the elderly who had low self-efficacy obtained results of 41 (38.7%). In addition, the results of the elderly who had a good quality of life were obtained with the results of 59 (55.7%) elderly people, while the elderly who had a poor quality of life with the results of 47 elderly people (44.3%). This study shows a meaningful relationship between self-efficacy and the quality of life of the elderly with hypertension (p=0.006). There is a meaningful relationship between self-efficacy and the quality of life of the elderly with hypertension.